Method for optimizing residual stress distribution of high-speed steel punch based on spheroidizing annealing process

By employing a process chain of cyclic spheroidizing annealing, stepped quenching, cryogenic treatment, and multi-stage tempering, the problem of uneven residual stress distribution in high-speed steel punches was solved, achieving low-cost stress optimization and performance improvement to meet the needs of high-performance tools.

CN120866612APending Publication Date: 2025-10-31HEBEI UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511030920.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-25
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

In existing technologies, the residual stress distribution of high-speed steel punches is uneven, which affects tool performance and lifespan. Furthermore, traditional processes are unable to effectively release the residual stress generated by extrusion processing, increasing production costs.

Method used

The process chain of cyclic spheroidizing annealing, stepped quenching, cryogenic treatment and multi-stage tempering is adopted. By controlling the heating and cooling rates, 70-90% of the residual stress is released, compressive stress is transformed into tensile stress, and the refinement and uniform distribution of carbides are promoted. Combined with multi-stage tempering, the material properties are optimized.

Benefits of technology

It significantly reduced the residual stress level of the punch, improved hardness and impact toughness, extended service life, and improved the overall performance of the material by refining the carbide structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120866612A_ABST
    Figure CN120866612A_ABST
Patent Text Reader

Abstract

The invention discloses a method for optimizing residual stress distribution of a high-speed steel punch based on a spheroidizing annealing process, and belongs to the technical field of metal material heat treatment. The method for optimizing the residual stress distribution of the high-speed steel punch based on the spheroidizing annealing process comprises a circulating spheroidizing annealing process, a quenching process, a subzero treatment process and a multi-stage tempering process, and aims at achieving the following purposes that punch machining residual stress is remarkably released, especially compressive stress concentration of geometric mutation areas (such as the root and the head), and the crack initiation risk is reduced; the microstructure uniformity is optimized, and the comprehensive mechanical property of the material is improved through carbide refining and dispersion distribution; the stress evolution rule under the synergistic effect of multiple processes is quantified, and accurate guidance is provided for process optimization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of heat treatment technology for metallic materials, and more specifically relates to a method for optimizing the residual stress distribution of high-speed steel punches based on spheroidizing annealing process. Background Technology

[0002] High-speed steel (HSS) is an alloy tool steel containing high levels of carbide elements (such as W, Mo, Cr, V, etc.), possessing high hardness, wear resistance, and high-temperature red hardness. A typical composition of M42 high-speed steel is 1.08% C, 9.30% Mo, and 7.85% Co, supplemented with elements such as Cr and V. Through the synergistic effect of carbide dispersion strengthening and matrix solid solution strengthening, it can maintain a sharp cutting edge during high-temperature, high-speed cutting and is widely used in the manufacture of high-precision tools.

[0003] However, the manufacturing of high-speed steel components requires multiple heat treatment processes, and the complex process chain can easily lead to significant residual stress within the material, affecting tool performance and lifespan. Residual stress originates from thermal stress and structural stress: thermal stress is caused by the temperature gradient between the surface and core of the material during heating or cooling; structural stress originates from the non-uniform volume change during phase transformation. Due to differences in cooling rates and non-uniform phase transformation, punches with complex geometries exhibit a significant gradient distribution of residual stress, making them prone to becoming weak points for crack initiation and propagation.

[0004] To address residual stress control in high-speed steel, academia and industry have proposed various process optimization strategies: spheroidizing annealing can spheroidize and uniformly distribute carbides, reducing material hardness and releasing processing stress; cryogenic treatment can promote the transformation of retained austenite to martensite, refining carbides and improving dimensional stability; multi-stage tempering can eliminate quenching stress and balance material toughness. However, existing research mostly focuses on the effects of single processes, lacking systematic research on the dynamic evolution mechanism under the synergistic effect of multiple processes. In particular, experimental data and predictive models for the local stress distribution characteristics in the punch geometry abrupt change region are scarce, leading to blind optimization of processes.

[0005] The existing technology has the following drawbacks: the residual stress generated by extrusion processing in the traditional process route is high and difficult to release; direct quenching without spheroidizing annealing leads to poor carbide distribution and reduces material toughness; although the existing cryogenic treatment process can improve residual stress, it cannot solve the problem of initial stress accumulation and increases production costs. Summary of the Invention

[0006] The purpose of this invention is to provide a method for optimizing the residual stress distribution of high-speed steel punches based on spheroidizing annealing process, so as to solve the problems existing in the prior art, achieve optimization of the residual stress distribution of high-speed steel punches at low cost, and improve the hardness and impact toughness of the material.

[0007] To achieve the above objectives, the present invention provides the following solution:

[0008] One of the technical solutions of this invention is to provide a method for optimizing the residual stress distribution of high-speed steel punches based on spheroidizing annealing process, comprising the following steps:

[0009] S1, under vacuum degree ≤ 5 × 10 -3 Under the condition of Pa, the high-speed steel punch is subjected to heating stage treatment and cooling stage treatment in sequence to complete one cycle of spheroidizing annealing. Repeat 3 to 5 cycles to achieve cyclic spheroidizing annealing.

[0010] S2. The high-speed steel punch after cyclic spheroidizing annealing is first heated and then cooled in a quenching medium to achieve step quenching treatment.

[0011] S3. The high-speed steel punch after the stepped quenching treatment is subjected to deep cryogenic treatment and four tempering treatments in sequence to obtain the high-speed steel punch with optimized residual stress distribution.

[0012] Preferably, the heating stage of step S1 includes: heating to Ac1+20℃ and holding for 15 minutes; the cooling stage of step S1 includes: cooling to Ac1-50℃ and holding for 15 minutes.

[0013] In this invention, Ac1 refers to the starting temperature of the transformation from pearlite to austenite when the high-speed steel punch is heated, which varies depending on the composition of the high-speed steel punch.

[0014] Preferably, in step S1: the heating rate of the first cycle of the heating stage is 60℃ / min, and the heating rate of the second and subsequent cycles is 30℃ / min; the cooling rate of the first cycle of the cooling stage is 30℃ / min, and the cooling rate of the second and subsequent cycles is 15℃ / min.

[0015] This invention can suppress carbide aggregation and ensure uniform carbide distribution by controlling the cooling rate during the cooling stage.

[0016] The purpose of the cyclic spheroidizing annealing described in this invention is to release the residual stress formed by the extrusion process. The cyclic spheroidizing annealing process releases 70-90% of the residual stress in the punch, and the direction of the residual stress changes from compressive stress to tensile stress. The cyclic spheroidizing annealing process promotes the refinement of carbides, increasing the proportion of carbides with a size <1.5μm to more than 55%, and ensuring uniform distribution.

[0017] Furthermore, after the cyclic spheroidizing annealing is completed, the process also includes a step of furnace cooling to room temperature (25±5℃).

[0018] Preferably, the heating in step S2 includes heating in a salt bath at 1150-1160°C, with the holding time calculated based on the thickness of the high-speed steel punch, specifically 30-35 s / mm, where the thickness is in mm.

[0019] Preferably, the cooling in the quenching medium in step S2 includes: holding the medium at 550-560°C for a period of time, where the holding time t = (1-1.5) × thickness, the thickness is in mm, and the holding time is in min.

[0020] Preferably, the quenching medium comprises a potassium nitrate-sodium nitrite mixed molten salt and nano-aluminum nitride, wherein the mass of the nano-aluminum nitride is 0.02-0.05% of the mass of the potassium nitrate-sodium nitrite mixed molten salt. The quenching medium can refine the quenched structure.

[0021] Preferably, in step S3: the cryogenic treatment is carried out in liquid nitrogen, and the cryogenic treatment time is 1.5 to 2 hours.

[0022] Preferably, the four tempering processes in step S3 include: holding at 530-540℃ for 1.5-2 hours, holding at 540-550℃ for 1.5-2 hours, holding at 520-530℃ for 1-1.5 hours, and holding at 500-510℃ for 1-1.5 hours.

[0023] The second technical solution of the present invention is to provide a high-speed steel punch with optimized residual stress distribution prepared by the above method.

[0024] The high-speed steel punch with optimized residual stress distribution prepared in this invention meets the following performance indicators: surface hardness HRC 64-66; residual stress difference in the X / Y direction ≤120MPa; carbides with a size <1.5μm account for ≥50% and are uniformly dispersed; uniform tensile stress of 50-150MPa is formed in the punch root region within 5mm from the end face; impact toughness is 28J / cm. 2 .

[0025] The mechanism of action of each stage described in this invention is as follows:

[0026] Cyclic spheroidizing annealing: Utilizing the principle of segregated eutectoids, the dissolved carbon in each cycle directly forms spherical carbide particles, rather than lamellar carbides. Compared to conventional isothermal annealing processes (see Example 2), this invention reduces the spheroidizing treatment time by more than 80%. Simultaneously, periodic thermal stress release reduces residual compressive stress in geometrically abrupt regions by 70-90% (effects as described in the example). Figure 6 Comparison data and Figure 7 As shown in the stress evolution curve), it is transformed into a uniform tensile stress field; by eliminating the work hardening introduced by extrusion molding, 70-90% of the residual compressive stress is released, and at the same time, the carbide size is refined to <1.5μm, and the proportion of carbides refined to <1.5μm is increased to more than 55% (the carbide refinement and proportion are as follows). Figure 8 As shown in the figure, a dispersion strengthening effect is formed, providing a uniform matrix structure for subsequent quenching.

[0027] Step-quenching treatment: Heating is followed by rapid cooling to avoid secondary carbide precipitation. Combined with the uniform and fine microstructure after cyclic spheroidizing annealing, carbide dissolution is more complete and martensitic transformation is more thorough during quenching. Experimental results show (e.g.) Figure 9 The XRD pattern shows that the martensite peaks are stronger after quenching using this process, and the combination... Figure 10 The data shows that the retained austenite content after quenching is 51.8%. Because the cyclic spheroidizing annealing process described in this invention promotes more complete dissolution of carbides during subsequent quenching heating, the carbon concentration in the austenite after quenching is higher, resulting in a significantly higher retained austenite content than the traditional process (51.8% vs. 45.2%). While this increases the total amount of retained austenite, it also provides more sufficient phase transformation potential for subsequent cryogenic treatment.

[0028] Cryogenic treatment: Promotes the further transformation of retained austenite into martensite (conversion rate ≥85%). Cryogenic treatment effectively promotes the transformation of retained austenite into martensite (change in retained austenite content is as follows). Figure 10 As shown, the content of residual austenite decreased from 51.8% to 4.31%, with a conversion rate as high as 91.7%, significantly higher than 85%, which ultimately significantly reduced the content of residual austenite and further improved hardness and dimensional stability.

[0029] Four-stage tempering treatment: Multiple tempering processes are employed to gradually eliminate the stress introduced by quenching and cryogenic treatment, and to strengthen and balance the material's toughness and hardness through carbide precipitation. The residual stress release rate after each tempering stage reaches 30-40%, ultimately reducing the overall residual stress level of the punch to <200 MPa. Cryogenic treatment combined with multi-stage tempering significantly improves the material's strength and toughness while eliminating quenching stress, achieving synergistic optimization of microstructure and properties.

[0030] The present invention discloses the following technical effects:

[0031] Residual stress optimization: The cyclic spheroidizing annealing process effectively releases the residual stress generated in the high-speed steel punch during extrusion, with a residual stress release rate of 70-90%. In easily damaged areas such as the root of the high-speed steel punch, the stress direction changes from compressive stress (400MPa) to tensile stress (100MPa). This helps to counteract the external stress experienced by the punch during use, delays the initiation and propagation of cracks, and thus extends the service life of the high-speed steel punch.

[0032] Microstructure Improvement: The cyclic spheroidizing annealing process promotes the formation and uniform distribution of small-sized carbides, refining the carbide size to <1.5μm and increasing its proportion to over 50%. This refinement and homogenization of the microstructure helps improve the hardness, toughness, and wear resistance of the high-speed steel punch, providing a good microstructure foundation for subsequent quenching and tempering processes.

[0033] Performance Enhancement: The high-speed steel punches after cyclic spheroidizing annealing exhibit excellent performance in terms of hardness and impact toughness. This demonstrates that optimizing the heat treatment process can significantly improve the overall performance of high-speed steel punches, meeting the requirements for high-performance punches.

[0034] In summary, this invention, through a process chain of cyclic spheroidizing annealing, quenching, cryogenic treatment, and multi-stage tempering, aims to achieve the following objectives:

[0035] Significantly releases residual stress from punch processing: especially compressive stress concentration in areas of geometric abrupt change (such as the root and head), reducing the risk of crack initiation; optimizes microstructure uniformity: improves the comprehensive mechanical properties of materials through the refinement and dispersion of carbides; quantifies the stress evolution law under the synergistic effect of multiple processes, providing precise guidance for process optimization. Attached Figure Description

[0036] Figure 1 Optimize the core process flow diagram for heat treatment of high-speed steel punches;

[0037] Figure 2 A comparison of temperature-time curves for different heat treatment processes of M42 high-speed steel punches;

[0038] Figure 3 The diagrams show conventional spheroidizing annealing and cyclic spheroidizing annealing processes. The left diagram shows conventional spheroidizing annealing, and the right diagram shows cyclic spheroidizing annealing.

[0039] Figure 4 A physical image of an M42 high-speed steel punch and a schematic diagram showing the location of residual stress.

[0040] Figure 5 The microstructure of M42 high-speed steel under different spheroidizing annealing pretreatment processes is shown in the figures. (a) is unannealed, OM; (b) is unannealed, SEM; (c) is after spheroidizing annealing, OM; and (d) is after spheroidizing annealing, SEM.

[0041] Figure 6 The residual stress measurement results at various points on the end surface of the M42 high-speed steel punch under different heat treatment processes;

[0042] Figure 7 The evolution of residual stress in the X and Y directions at various points of an M42 high-speed steel punch under different heat treatment conditions;

[0043] Figure 8 Comparison of the size distribution of small-sized carbides in M42 high-speed steel punches under different heat treatment conditions;

[0044] Figure 9The XRD patterns of M42 high-speed steel punches under different heat treatment conditions are shown. The left figure shows the XRD patterns of M42 high-speed steel punches at each treatment stage of production line two, and the right figure shows the XRD patterns of M42 high-speed steel punches at each treatment stage of production line one.

[0045] Figure 10 The variation of residual austenite content in M42 high-speed steel punches under different heat treatment conditions;

[0046] Figure 11 The microstructures of M49 high-speed steel after conventional spheroidizing annealing and cyclic spheroidizing annealing are shown. (a) is conventional spheroidizing annealing (control group), and (b) is cyclic spheroidizing annealing (experimental group).

[0047] Figure 12 The effect of different annealing processes on the impact toughness of M42 high-speed steel. Detailed Implementation

[0048] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0049] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0050] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0051] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0052] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0053] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.

[0054] Unless otherwise specified, all raw materials used in the following embodiments of the present invention are commercially available products, and the source of commercially available products does not affect the technical effect of the present invention.

[0055] Unless otherwise specified, the room temperature involved in this invention is 25±5℃.

[0056] Figure 1 A flowchart for optimizing the core heat treatment process of high-speed steel punches.

[0057] Figure 2 A comparison of temperature-time curves for different heat treatment processes of M42 high-speed steel punches.

[0058] For the M42 high-speed steel used in the embodiments of the present invention, its Ac1 point is approximately 805-815℃. Therefore, the temperature of the heating stage is preferably 825-835℃, and the temperature of the cooling stage is preferably 720-730℃.

[0059] Example 1

[0060] This embodiment provides a test of the effect of whether or not a cyclic spheroidizing annealing process is performed on the performance of high-speed steel punches:

[0061] 1. Experimental materials

[0062] The experiment used M42 high-speed steel punches as the research object, and their chemical composition is shown in Table 1. M42 high-speed steel has excellent hardness, wear resistance and high-temperature red hardness, and is widely used in the manufacture of high-precision punches, drills, milling cutters and other tools.

[0063] Table 1. Chemical composition (wt.%) of M42 high-speed steel

[0064] steel grades C Si Mn Cr Mo V W Co P S M42 1.08 0.29 0.33 3.88 9.30 1.10 1.32 7.85 0.018 0.002

[0065] The experiment used Φ50×200mm M42 high-speed steel extrusion billets.

[0066] 2. Process Flow

[0067] The experiment was set up with two production lines:

[0068] Production Line 1: After extrusion and before the first quenching, a cyclic spheroidizing annealing process is applied (see...). Figure 3 (Schematic diagram of the cyclic spheroidizing annealing process).

[0069] Production Line 2: No cyclic spheroidizing annealing process was applied.

[0070] By comparing the residual stress and microstructure evolution of samples from two production lines, the correlation between the process and residual stress and microstructure was clarified. Specific process parameters are shown in Table 2.

[0071] Table 2 Processing parameters of the two production lines

[0072]

[0073]

[0074] 3. Measurement Method

[0075] Residual stress measurement: The residual stress of the punch before and after heat treatment was measured using a Rigaku Automatic-II X-ray diffractometer (Japan). Test conditions were flexibly selected based on different requirements such as sample type, penetration depth, and measurement area. The experiment focused on locations 1, 6, and 9 of the punch that are prone to damage. Figure 4 As shown, ( Figure 4 (A physical image of an M42 high-speed steel punch and a schematic diagram of residual stress location measurement) The residual stress distribution was precisely measured using a 0.5mm light spot.

[0076] Microstructure observation: The phase composition and relative content of the samples were analyzed using a Rigaku D / max-2500 / PC X-ray diffractometer, with Co-Kα as the radiation target and a scanning speed set to 2° / min. The volume fraction (Vγ) of the retained austenite phase and the carbon content (Cγ) in the retained austenite were calculated using specific formulas. Furthermore, to visually compare the effects of different pretreatment processes on the initial microstructure of M42 high-speed steel, observations were performed using an optical microscope (OM) and a scanning electron microscope (SEM), with 4wt% nitric acid alcohol as the etching solution. Figure 5 Typical microstructures of samples without spheroidizing annealing (production line 2) and samples treated with cyclic spheroidizing annealing (production line 1) are shown.

[0077] 4. Experimental Results

[0078] Residual stress test results:

[0079] Figure 6This document presents the residual stress measurements at various points on the end surface of an M42 high-speed steel punch under different heat treatment processes. The values ​​are as follows: Before heat treatment: Residual stress of the M42 high-speed steel punch before the start of the experiment; After annealing: Residual stress of the M42 high-speed steel punch after spheroidizing annealing in the first cycle of production line one; After the first tempering (without annealing): Residual stress of the M42 high-speed steel punch after the first tempering in production line two; After the first tempering (after annealing): Residual stress of the M42 high-speed steel punch after the first tempering in production line one; After the second tempering (without annealing): Residual stress of the M42 high-speed steel punch after the second tempering in production line two. The residual stress of the steel punch is shown in the following diagrams: after the second tempering (after annealing), the residual stress of the M42 high-speed steel punch after the second tempering in production line 1 is shown in the diagram; after the third tempering (without annealing), the residual stress of the M42 high-speed steel punch after the third tempering in production line 2 is shown in the diagram; after the fourth tempering (without annealing), the residual stress of the M42 high-speed steel punch after the fourth tempering in production line 2 is shown in the diagram; and after the fourth tempering (after annealing), the residual stress of the M42 high-speed steel punch after the fourth tempering in production line 1 is shown in the diagram.

[0080] Figure 7 The evolution of residual stress in the X and Y directions at various points of an M42 high-speed steel punch under different heat treatment conditions is shown, where 1X represents Figure 4 The evolution of residual stress in the X direction at point 1, where 1Y represents Figure 4 The evolution of residual stress in the Y direction at point 1, 3X represents Figure 4 The evolution results of residual stress in the X direction at 3 points, 3Y represents Figure 4 The evolution results of residual stress in the Y direction at 3 points, 6X represents Figure 3 The evolution results of residual stress in the X direction at 6 points, where 6Y represents Figure 4 The evolution results of residual stress in the Y direction at 6 points, 9X represents Figure 4 The evolution results of residual stress in the X direction at point 9, where 9Y represents Figure 4 The evolution results of residual stress in the Y direction at point 9. Figure 7 In the diagram, "no annealing" represents production line two, "annealing" represents production line one, and "preheating", "annealing", "1st tempering", "2nd tempering", "3rd tempering", and "4th tempering" respectively represent "before the experiment begins", "cyclic spheroidizing annealing", "first tempering", "second tempering", "third tempering", and "fourth tempering".

[0081] Root region: After cyclic spheroidizing annealing (corresponding to production line one), the stress state in the punch root region was significantly optimized. The X-axis stress value changed to +95MPa, and the Y-axis stress value changed to +88MPa. The stress direction successfully changed from the initial compressive stress (250-400MPa) in the extrusion state to tensile stress, and the stress level was significantly reduced to below 100MPa. In the subsequent four-stage tempering process (production line one, after annealing), the root region (such as...) Figure 7 The tensile stress state (shown in 9X and 9Y) was basically maintained, but the specific values ​​fluctuated slightly, and the overall tensile stress level remained low. In contrast, the root region of production line two, which did not undergo spheroidizing annealing, may exhibit higher compressive stress in the Y direction after undergoing four stages of tempering, and the stress state in the X direction also differs from that of production line one (see [reference to production line one] for specific values ​​and trends). Figure 6 and Figure 7 This shift in stress state, especially at vulnerable points such as the punch root, optimizes the initial compressive stress from a large one to a moderate tensile stress (such as around 100 MPa or even lower), effectively reducing the risk of crack initiation and extending the punch's service life.

[0082] Other locations: At other measuring points on the punch (such as...) Figure 7 As shown at points 1, 3, and 6, after cyclic spheroidizing annealing, the residual stress was also significantly released. During the subsequent four-stage tempering process (production line one, after annealing), the residual stress levels at these points further stabilized at lower values ​​and became more uniformly distributed. Compared to production line two, which did not undergo spheroidizing annealing (refer to...), the residual stress levels at these points were significantly reduced. Figure 6 and Figure 7 (Data from each tempering stage) After each tempering, the overall residual stress level on the surface of the punch is lower and the distribution is more ideal, which is beneficial to improving the overall service performance of the punch.

[0083] Metallographic test results:

[0084] Figure 8 The size distribution of small carbides in M42 high-speed steel punches under different heat treatment conditions is compared. Unannealed represents production line 2, and annealed represents production line 1.

[0085] Carbide size: After cyclic spheroidizing annealing, the average carbide size in the punch structure is 1.2μm, and the proportion of small carbides (<1.5μm) reaches 55%, forming a uniform and dispersed distribution, which significantly improves the microstructure uniformity of the steel.

[0086] Figure 9 The images show the XRD patterns of M42 high-speed steel punches under different heat treatment conditions. The left image shows the XRD pattern of production line two (without cyclic spheroidizing annealing); the right image shows the XRD pattern of production line one (in this invention, cyclic spheroidizing annealing was performed).

[0087] Figure 9 The XRD patterns of M42 high-speed steel punches under different heat treatment conditions are shown. The left image is the XRD pattern of production line two (without cyclic spheroidizing annealing); the right image is the XRD pattern of production line one (in this invention, cyclic spheroidizing annealing was performed). Figure 9 It can be seen that the sample from production line 1, which has undergone cyclic spheroidizing annealing pretreatment, may exhibit stronger martensite diffraction peaks and fewer retained austenite diffraction peaks in the quenched state. At the same time, during the tempering process, the carbide precipitation type or diffraction peak characteristics of the two samples may also differ. For example, production line 1 may show more diffuse secondary carbide diffraction peaks.

[0088] Figure 10 The variation of residual austenite content in M42 high-speed steel punches under different heat treatment states is shown. In this case, non-annealing represents production line 2, annealing represents production line 1, and preheating, tempering 1, tempering 2, tempering 3, and tempering 4 represent preheating, first tempering, second tempering, third tempering, and fourth tempering, respectively.

[0089] Depend on Figure 10 It can be seen that in the extruded state (before hot forming), the material initially contains 4.11% retained austenite. The two process routes exhibit different evolution paths in subsequent treatments:

[0090] For production line one (annealing): Quenching produced a large amount of retained austenite (up to 51.8%). After cryogenic treatment, the retained austenite content dropped sharply to 4.31%. During the subsequent multi-stage tempering process, the retained austenite content fluctuated, eventually stabilizing at a low level of 1.75% after the fourth tempering.

[0091] For production line two (non-annealed): the residual austenite content after quenching was 45.2%, lower than that of production line one. After cryogenic treatment, its content dropped to 2.08%, even lower than that of the first production line. Its tempering process also showed similar fluctuations, and finally, after the fourth tempering, the residual austenite content was 1.67%.

[0092] In summary, the spheroidizing annealing pretreatment (production line 1) resulted in more retained austenite after quenching. This is likely because spheroidal carbides are more easily dissolved, leading to a higher carbon content in the austenite and thus lowering the Ms point. However, despite the different evolution paths, both process routes, after complete cryogenic and four-stage tempering treatments, ultimately controlled the retained austenite content to an extremely low level below 2%, which is crucial for improving the dimensional stability and final hardness of the material.

[0093] Performance test results:

[0094] Surface hardness: The surface hardness of the punches after final heat treatment in Production Line 1 (including spheroidizing annealing) reached HRC 65.2. In contrast, the hardness of the punches in Production Line 2 (without spheroidizing annealing) was HRC 64.8, with some fluctuation. The hardness value of Production Line 1 was not only slightly higher, but also more uniformly and stably distributed, indicating that the spheroidizing annealing pretreatment improved the hardness uniformity of the material.

[0095] Impact toughness: Impact toughness test results show that the impact toughness of the punches after cyclic spheroidizing annealing on the production line reaches 28 J / cm. 2 Compared to 21J / cm of production line two 2 The improvement was 33.3%, which is significant and indicates that the material's impact resistance has been greatly enhanced.

[0096] 5. Results Analysis

[0097] Residual stress optimization: The cyclic spheroidizing annealing process effectively released the residual stress generated in the punch during extrusion. (Comparison) Figure 5 The stress data before and after heat treatment can be quantitatively analyzed. For example, at point 9 at the punch root, the initial compressive stress before heat treatment is as high as -400 MPa, while after annealing it transforms into a tensile stress of +88 MPa, with stress release exceeding 100% of the initial value. A comprehensive evaluation of all points shows that the residual stress release rate generally reaches 70-90%. In easily damaged areas such as the punch root, the stress direction changes from high compressive stress to low tensile stress. This helps to offset the external compressive stress load on the punch during use, thereby delaying crack initiation and propagation, and extending the punch's service life.

[0098] Microstructure Improvement: Cyclic spheroidizing annealing promotes the formation and uniform distribution of small-sized carbides, refining the carbide size to <1.5μm and increasing its proportion to 55%. This refinement and homogenization of the microstructure helps improve the material's hardness, toughness, and wear resistance, providing a good microstructure basis for subsequent quenching and tempering processes.

[0099] Performance Enhancement: The punches after spheroidizing annealing exhibit excellent performance in terms of hardness and impact toughness. This indicates that by optimizing the heat treatment process, the overall performance of M42 high-speed steel punches can be significantly improved, meeting the requirements for high-performance punches.

[0100] Example 2: Comparison with conventional spheroidizing annealing process

[0101] To further demonstrate the superiority of the cyclic spheroidizing annealing process proposed in this invention, this embodiment compares it with the conventional isothermal spheroidizing annealing process.

[0102] Control group:

[0103] The same M42 high-speed steel extruded billet as in Example 1 was subjected to conventional isothermal spheroidizing annealing. The specific process was as follows: heating to 850°C and holding for 4 hours; then furnace cooling to 730°C and holding for 4 hours; finally air cooling to room temperature. The total holding time was 8 hours, and the total annealing time exceeded 8 hours.

[0104] Experimental group:

[0105] The cyclic spheroidizing annealing process of the present invention is the same as that in Example 1, with a total holding time of only 1.5h (15min × 3 heating cycles + 15min × 3 cooling cycles).

[0106] The other treatment steps for the control group and the experimental group were the same as in Example 1.

[0107] Result comparison:

[0108] 1. Comparison of production efficiency

[0109] The cyclic annealing process of the present invention (total holding time 1.5h) reduces the processing time by more than 80% compared with conventional isothermal annealing (total holding time 8h), significantly improving production efficiency.

[0110] 2. Microstructural Comparison

[0111] The microstructures formed by the two processes are significantly different, specifically as follows: Figure 11 As shown.

[0112] Figure 11 The microstructures of M49 high-speed steel after conventional spheroidizing annealing and cyclic spheroidizing annealing are shown. (a) is conventional spheroidizing annealing (control group), and (b) is cyclic spheroidizing annealing (experimental group).

[0113] exist Figure 11 In (a), after conventional isothermal spheroidizing annealing, the control group exhibited large and unevenly distributed carbides in its microstructure, with a large number of coarse, irregular blocky carbides that severely disrupted the continuity of the matrix. Metallographic analysis showed that fine carbides with a size less than 1.5 μm accounted for only 40%.

[0114] exist Figure 11 In (b), after processing by the process of the present invention, the microstructure is significantly optimized, and the carbides exhibit fine, diffuse, and uniform distribution, with a more rounded spherical shape. Metallographic analysis shows that carbides with a size less than 1.5 μm account for 55%, with an average size of approximately 1.2 μm.

[0115] 3. Comparison of mechanical properties

[0116] The optimized microstructure leads to a significant improvement in subsequent mechanical properties, such as impact toughness. Figure 12 As shown.

[0117] Figure 12 The effect of different annealing processes on the impact toughness of M42 high-speed steel.

[0118] Depend on Figure 12 It can be seen that the punch using the annealing process of this invention achieves a final impact toughness of 28 J / cm. 2 The punches annealed using the control group method exhibited a final impact toughness of only 24 J / cm. 2 .

[0119] The performance improvement is attributed to the process of this invention achieving, as Figure 11 The superior microstructure shown in (b) effectively inhibits crack propagation due to its finely dispersed carbides, while the control group showed... Figure 11 The coarse carbides shown in (a) can become crack initiation sites, reducing the toughness of the material.

[0120] In summary, compared with existing technologies, the cyclic spheroidizing annealing process of the present invention not only significantly shortens the annealing time and improves production efficiency, but more importantly, it achieves the following results: Figure 11 The fine, dispersed, and uniform carbide structure shown in (b) significantly improves the impact toughness of the material (see Figure 12 This invention lays an excellent microstructure foundation for the preparation of high-performance M42 high-speed steel punches, solving the technical problems of long processing time and poor microstructure in conventional processes. Microstructure effect: After treatment with this invention, the average size of carbides is 1.2 μm, and the proportion of carbides with a size <1.5 μm reaches 55%.

[0121] Conclusion: The cyclic spheroidizing annealing process of the present invention not only significantly shortens the annealing time, but also obtains finer and more dispersed carbide structures, laying a better microstructure foundation for the preparation of high-performance punches.

[0122] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.

[0123] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for optimizing the residual stress distribution of high-speed steel punches based on spheroidizing annealing process, characterized in that, Includes the following steps: S1, under vacuum degree ≤ 5 × 10 -3 Under the condition of Pa, the high-speed steel punch is subjected to heating stage treatment and cooling stage treatment in sequence to complete one cycle of spheroidizing annealing. Repeat 3 to 5 cycles to achieve cyclic spheroidizing annealing. S2. The high-speed steel punch after cyclic spheroidizing annealing is first heated and then cooled in a quenching medium to achieve step quenching treatment. S3. The high-speed steel punch after the stepped quenching treatment is subjected to deep cryogenic treatment and four tempering treatments in sequence to obtain the high-speed steel punch with optimized residual stress distribution.

2. The method according to claim 1, characterized in that, The heating stage of step S1 includes: heating to Ac1+20℃ and holding for 15 minutes; the cooling stage of step S1 includes: cooling to Ac1-50℃ and holding for 15 minutes.

3. The method according to claim 2, characterized in that, In step S1: the heating rate of the first cycle of the heating stage is 60℃ / min, and the heating rate of the second and subsequent cycles is 30℃ / min; the cooling rate of the first cycle of the cooling stage is 30℃ / min, and the cooling rate of the second and subsequent cycles is 15℃ / min.

4. The method according to claim 1, characterized in that, The heating in step S2 includes heating in a salt bath at 1150-1160°C, with the holding time calculated based on the thickness of the high-speed steel punch, specifically 30-35 s / mm, where the thickness is in mm.

5. The method according to claim 1, characterized in that, Step S2, cooling in the quenching medium, includes: holding the medium at 550-560℃ for a period of time, where the holding time t = (1-1.5) × thickness, the thickness is in mm, and the holding time is in min.

6. The method according to claim 5, characterized in that, The quenching medium includes a potassium nitrate-sodium nitrite mixed molten salt and nano-aluminum nitride, wherein the mass of the nano-aluminum nitride is 0.02 to 0.05% of the mass of the potassium nitrate-sodium nitrite mixed molten salt.

7. The method according to claim 1, characterized in that, In step S3: the cryogenic treatment is carried out in liquid nitrogen for 1.5 to 2 hours.

8. The method according to claim 1, characterized in that, The four tempering processes described in step S3 include: holding at 530–540℃ for 1.5–2 hours, holding at 540–550℃ for 1.5–2 hours, holding at 520–530℃ for 1–1.5 hours, and holding at 500–510℃ for 1–1.5 hours.

9. The high-speed steel punch with optimized residual stress distribution prepared by the method according to any one of claims 1 to 8.

10. The high-speed steel punch with optimized residual stress distribution according to claim 9, characterized in that, The optimized high-speed steel punch with residual stress distribution meets the following performance indicators: surface hardness HRC 64-66; residual stress difference in the X / Y direction ≤120MPa; carbides with a size <1.5μm account for ≥50% and are uniformly dispersed; uniform tensile stress of 50-150MPa is formed in the punch root region within 5mm from the end face; impact toughness is 28J / cm. 2 .

Citation Information

Cited By

  • Aluminum-containing high-boron high-speed steel oil field oil well pump and preparation method thereof

    CN121496263A